Implementation of Micro Syari'ah People's Business Credit (KUR) Financing at Bank Syari'ah Indonesia KCP Cirebon Plered 1 - Shabrina Fatimah Amini (Al-Fadilah: Islamic Economics Journal, 2023)
Bank Syariah Indonesia (BSI) KCP Cirebon Plered 1 has a variety of products. Therefore, KUR financing which is able to solve customer capital or financial problems, makes Bank Syariah Indonesia (BSI) KCP Cirebon Plered 1 one of the sharia banks of choice for prospective customers. The contract implemented by BSI KCP Plered I is the mudharabah contract, where the bank as shahibul maal entrusts a certain amount of capital to the customer as mudharib. Around 1,004 UMKM in the Cirebon area, including businesses that sell daily necessities, apparel, food and workshops, have received financing from BSI. The method used in this study is a qualitative descriptive method, where this research aims to describe and understand a phenomenon even further, in this case related to the Implementation of Micro Syari’ah Business Credit Financing (KUR) at Indonesian Syari’ah Bank KCP Cirebon Plered 1. Data collection techniques in this study were carried out by interviews, observation and documentation. Based on actual records, it can be said that BSI KCP Cirebon Plered 1 has succeeded in providing financing to customers. This is indicated by the financing requirements, the lending process, the realization of the financing, the amount of administrative fees, bank officer services, bank locations, guarantees/collaterals, knowledge and participation of customers/prospective customers, as well as providing a beneficial influence on customers